2021
DOI: 10.26434/chemrxiv.14442767
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Snapshots of Ce70 Toroid Assembly from Solids and Solution

Abstract: Crystallization at the solid-liquid interface is difficult to spectroscopically observe and therefore challenging to understand and ultimately control at the molecular level. The Ce70-torroid formulated [CeIV70(OH)36(O)64(SO4)60(H2O)10] 4- , part of a larger emerging family of MIV70- materials (M=Zr, U, Ce), presents such an opportunity. We have elucidated assembly mechanisms by X-ray scattering (small-angle scattering and total scattering) of solutions and solids, as well as crystallizing and identifying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…Studies have shown that the high crystallinity allows the cerium fragments of the Ce 70 toroid to be crystallized and identified by single-crystal X-ray diffraction, which is highly significant for cluster formation understanding. 26 A series of heterometallic Ce IV /M (M = Mo VI , Re VII , and V V )-oxo clusters, of which the Ce IV /V V cluster catalyzed the oxidation of thioanisole, was synthesized and studied. 27 The electron deficiency on the Ce IV centers greatly increases the electrophilicity of the V V centers, thus enhancing the cluster's catalytic performance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Studies have shown that the high crystallinity allows the cerium fragments of the Ce 70 toroid to be crystallized and identified by single-crystal X-ray diffraction, which is highly significant for cluster formation understanding. 26 A series of heterometallic Ce IV /M (M = Mo VI , Re VII , and V V )-oxo clusters, of which the Ce IV /V V cluster catalyzed the oxidation of thioanisole, was synthesized and studied. 27 The electron deficiency on the Ce IV centers greatly increases the electrophilicity of the V V centers, thus enhancing the cluster's catalytic performance.…”
Section: ■ Introductionmentioning
confidence: 99%
“…22−24 For Ce 70 , the use of counterions has afforded the isolation of fragments that provide insight into selfassembly mechanisms. 25 The different ionic behavior and hydration enthalpies for the alkali metals have been shown to influence the formation of thorium nitrato complexes and U 6sulfate lattices. 26 Hard, or highly acidic, U IV , Ce IV , and Pu IV yielded larger molecular clusters, including U 12 , U 14 , 27 and U 16 ; 28,29 7 in addition to the ubiquitous hexamers; all of these resemble the parent fluorite-type oxide.…”
Section: ■ Introductionmentioning
confidence: 99%
“…High-nuclearity 3d-4f metal oxide/hydroxide clusters (M > 25) have attracted extensive research attention because of their fascinating structures and interesting properties. [1][2][3][4][5][6][7][8][9][10] Among the different properties, a particularly interesting one is the molecular magnetocaloric effect (MCE). [11][12][13][14][15] The MCE is a phenomenon that leads to a reversible temperature change when a material is exposed to a changing magnetic field.…”
Section: Introductionmentioning
confidence: 99%